Tityus serrulatus (Scorpion): From the Crude Venom to the Construction of Synthetic Peptides and Their Possible Therapeutic Application Against Toxoplasma gondii Infection - de Assis, Diego Rodney Rodrigues; Pimentel, Pollyana Maria de Oliveira; dos Reis, Pablo Victor Mendes; Rabelo, Rayane Aparecida Nonato; Vitor, Ricardo Wagner Almeida; Cordeiro, Marta do Nascimento; Felicori, Liza Figueiredo; Olórtegui, Carlos Delfin Chávez; Resende, Jarbas Magalhães; Teixeira, Mauro Martins; Borges, Márcia Helena; de Lima, Maria Elena; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasmosis, caused by Toxoplasma gondii, is a major public concern owing to its neurotropic nature and high morbidity and mortality rates in immunocompromised patients and newborns. Current treatment for this disease is inefficient and produces side effects. Inflammatory mediators produced during T. gondii infection (e.g., cytokines and nitric oxide) are crucial in controlling parasite replication. In this context, Tityus serrulatus venom (TsV) induces the production of inflammatory mediators by immune cells. Thus, this study aimed to isolate and identify the components of TsV with potential anti-T. gondii activity. TsV was extracted from scorpions and lyophilized or loaded onto a column to obtain its fractions. TsV subfractions were obtained using chromatography, and its amino acid sequence was identified and applied to peptide design using bioinformatics tools. The C57BL/6 mice and their harvested macrophages were used to test the anti-Toxoplasma activity of TsV components and peptides. TsV and its fraction F6 attenuated the replication of tachyzoites in macrophages and induced nitric oxide and cytokine (IL-12, TNF, and IL-6) production by infected cells, without host cell toxicity. Moreover, Su6-B toxin, a subfraction of F6, demonstrated anti-T. gondii activity. The partially elucidated and characterized amino acid sequence of Sub6-B demonstrated 93% similarity with T. serrulatus 2 toxin (Ts2). Ts2 mimetic peptides (“Pep1,” “Pep2a,” and “Pep2b”) were designed and synthesized. Pep1 and Pep2a, but not Pep2b, reduced the replication of tachyzoites in macrophages. In vivo, treatment of T. gondii-infected mice with Pep1, Pep2a, or Pep2b decreased the number of cerebral cysts and did not induce hepatotoxicity in the animals. Taken together, our data show promising immunomodulatory and antiparasitic activity of TsV that could be explored and applied in future therapies for treating infectious parasitic diseases such as toxoplasmosis.